Carbamazepine and Methylphenidate Levels in ADHD - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
A carbamazepine (CBZ)-induced lowering of methylphenidate (MPH) serum levels in a 13-year-old female treated for ADHD and aggressive behavior, is reported from the Eastern Pennsylvania Psychiatric Institute, Philadelphia.